Study on mechanical properties of macro‐synthetic fiber‐reinforced iron ore tailings concrete. (29th October 2021) - Zhao, Jiangshan; Su, Youpo; Shi, Yunxing; Wang, Qingxuan; Ni, Kun
Abstract: Macro‐synthetic fiber‐reinforced iron ore tailings (IOT) concrete is an environment‐friendly building material featured by recycling IOT and improving performance of IOT concrete due to fiber incorporation. In this study, the mechanical properties of macro‐synthetic fiber‐reinforced concrete incorporating IOT were investigated. Two different replacement ratios of IOT (i.e., 0% and 50%) and six types of macro‐synthetic fibers at 1.0 vol% were adopted to investigate the effects of IOT, aspect ratio, elastic modulus, and tensile strength of macro‐synthetic fibers on mechanical properties of concrete. The results indicate that the concrete with IOT for natural sand (NS) replacement in 50 wt% demonstrates no loss in compressive strength and a minor loss of 7.67% in fracture energy, but the incorporation of IOT lowers splitting tensile strength and limit of proportionality, especially the splitting tensile strength with a decrease of 18.50%. The splitting tensile strength, equivalent flexural tensile strength, residual flexural tensile strength, and fracture energy were notably improved by adding macro‐synthetic fibers. Experimental results using Tukey test and Student's t test demonstrated that the fiber aspect ratio was more effective in improving equivalent flexural tensile strength, residual flexural tensile strength, and fracture energy than the elastic modulus and tensile strength of fibers, and the residual flexural tensile strength f R, 4 was enhanced by 146.34% when increasing the fiber aspect ratio from 36 to 60.